REVIEW AKTIVITAS ANTIBAKTERI EKSTRAK DAUN SIRIH HIJAU (Piper betle L.) METODE DIFUSI DAN MIKRODILUSI - Ni Luh Putu Taksayani Putri; Ni Luh Putu Vidya Paramita (JOURNAL SCIENTIFIC OF MANDALIKA (JSM), 2023)
Green betle plant (Piper betle L.) is a type of plant that is widely used for medicine. Parts of the betel plant (Piper betle L.) such as roots, seeds, and leaves have potential for treatment, but the most frequently used are the leaves. Empirically betel leaves are used by the community as an antibacterial. There are many literature and research studies that report the antibacterial activity of green betel leaves. In this review, we will discuss green betel leaf extract using various solvents using two antibacterial methods, namely the diffusion and microdilution methods. Library searches were carried out using secondary data with databases in the form of Pubmed, Google Scholar, Elsevier, and Science Direct. The results of the literature review stated that in the diffusion method, the highest antibacterial activity of green betel leaf extract was shown in the use of ethanol solvent with which had the highest growth inhibition of 33 mm against Staphylococcus aureus bacteria. Whereas with the microdilution method, the antibacterial activity of green betel leaf extract using ethanol and metanol solvents showed MIC value at 312 μg/mL.